Theorists of Postcolonialism Critique on the Eurocentric understanding of ‘history’ - Abdulrahman, Karwan Fatah; Mohammed, Adnan Amin (Journal of Current Social and Political Issues, 2023)
Centuries ago, Eurocentric ideas asserted Europe's centrality in world history, positing Western civilization as the inevitable guide for humanity. However, postcolonial theorists from the late twentieth century critically challenged Eurocentrism, arguing against its biased categorization of 'others' at the margins of global history. Through key postcolonial historical writings, these scholars have deeply probed Eurocentric understandings, striving to decentralize Europe's narrative in three main fields: Subaltern studies, Orientalism, and Race. To enhance the breadth and depth of this critique, the present research employs a rigorous historical research methodology. In Subaltern studies, primary sources and oral histories are meticulously examined to recover the voices of marginalized groups, contributing to a nuanced understanding of historical events. Orientalism is scrutinized through the analysis of historical texts, artworks, and cultural artifacts, revealing the constructed nature of Eurocentric interpretations. The study of Race involves archival research and critical analysis of historical documents to trace the evolution of racial ideologies. By applying these historical research methods, this study aims to extend the postcolonial critique beyond theoretical discourse, emphasizing its engagement with historical realities obscured by Eurocentric perspectives. The research seeks to underscore the significance of a methodologically rigorous approach in reshaping historical narratives, acknowledging the integral role of non-European nations in shaping the course of history and fostering a more inclusive historiography.